2020
DOI: 10.7150/ijbs.40643
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Akt2 in the Protective Effect of Fenofibrate against Diabetic Nephropathy

Abstract: Fenofibrate (FF) protects against diabetic nephropathy (DN) in type 1 diabetic (T1D) mice by upregulating the expression of fibroblast growth factor 21 (FGF21), leading to the activation of the Akt-mediated Nrf2 antioxidant pathways. Here, we examined which isoforms of Akt contribute to FF activation of FGF21-mediated renal protection by examining the phosphorylation and expression of three isoforms, Akt1, Akt2, and Akt3. T1D induced by a single intraperitoneal dose of streptozotocin (STZ) resulted in reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…PPAR-α agonist fenofibrate is known as an important lipidlowering drugs in clinical. Moreover, PPAR-α agonist fenofibrate has been proven to prevent DN and reduce urinary albumin in diabetic patients (26,27) and in diabetic mice (29)(30)(31)(32), which is independent of the effect on lipid-lowering. In current research, mice in different groups were similar in total cholesterol (TC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPAR-α agonist fenofibrate is known as an important lipidlowering drugs in clinical. Moreover, PPAR-α agonist fenofibrate has been proven to prevent DN and reduce urinary albumin in diabetic patients (26,27) and in diabetic mice (29)(30)(31)(32), which is independent of the effect on lipid-lowering. In current research, mice in different groups were similar in total cholesterol (TC).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our previous research also found that fenofibrate reduced microalbuminuria in patients with type 2 diabetes ( 28 ). In addition, PPAR-α agonists have been demonstrated to prevent DN and reduce proteinuria in both type 1 and type 2 diabetic animals ( 29 32 ). Nevertheless, the mechanism of how PPAR-α agonist fenofibrate prevents DN has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“… 57 Unfortunately, the therapeutic potential of FGF21 for OS in CKD in humans has not yet been studied, possibly due to its instability and short half-life. 58 Furthermore, to be able to consider FGF21 as a treatment in CKD, it is necessary to better understand the role of this growth factor in the mechanisms of the disease. The results of this study suggest that serum FGF21 is associated to OS markers in CKD; however, longitudinal studies that allow evaluation of causal associations would bring valuable information in this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 is a pivotal factor in oxidative stress response. Increasing evidence showed that Nrf2 displayed cytoprotective effects when cells were exposed adverse condition [31][32][33][34]. Nrf2 regulates ranges of antioxidants gene expression via binding to antioxidant response element.…”
Section: Discussionmentioning
confidence: 99%